2017
DOI: 10.3390/nu9111165
|View full text |Cite
|
Sign up to set email alerts
|

Precision Nutrition and Omega-3 Polyunsaturated Fatty Acids: A Case for Personalized Supplementation Approaches for the Prevention and Management of Human Diseases

Abstract: Background: Dietary essential omega-6 (n-6) and omega-3 (n-3) 18 carbon (18C-) polyunsaturated fatty acids (PUFA), linoleic acid (LA) and α-linolenic acid (ALA), can be converted (utilizing desaturase and elongase enzymes encoded by FADS and ELOVL genes) to biologically-active long chain (LC; >20)-PUFAs by numerous cells and tissues. These n-6 and n-3 LC-PUFAs and their metabolites (ex, eicosanoids and endocannabinoids) play critical signaling and structural roles in almost all physiologic and pathophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 203 publications
3
96
0
1
Order By: Relevance
“…These 2 families each encompass fatty acids with varying carbon chain length and degree of unsaturation. Supplemental Figure S1 shows PUFA biosynthesis, detailing the omega-6 and omega-3 pathways and the names of the main PUFA, as well as the elongation and the desaturation activities [1][2][3]. Briefly, the omega-6 PUFA linoleic acid (LA) and the omega-3 PUFA alpha-linolenic acid (ALA) from the diet are the key substrates that enter the pathways leading to the synthesis of the main long-chain PUFA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These 2 families each encompass fatty acids with varying carbon chain length and degree of unsaturation. Supplemental Figure S1 shows PUFA biosynthesis, detailing the omega-6 and omega-3 pathways and the names of the main PUFA, as well as the elongation and the desaturation activities [1][2][3]. Briefly, the omega-6 PUFA linoleic acid (LA) and the omega-3 PUFA alpha-linolenic acid (ALA) from the diet are the key substrates that enter the pathways leading to the synthesis of the main long-chain PUFA.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it has been claimed that the lack of conclusive evidence obtained in the meta-analyses may be due to several biases, including not only the poor quality of some of the meta-analyzed trials, but also other relevant factors such as the unmeasured role of genetic polymorphisms influencing the effect of dietary PUFA [1]. The potential role of FADS genetic polymorphism in determining the effects of dietary and pharmacological PUFA on several cardiovascular risk factors and outcomes, have been investigated by several studies [1,[60][61][62][63][64][65]. Among them, a post-hoc analysis from the OMEGA-REMODEL RCT, investigating the effect of high-dose of omega-3 PUFA post-acute myocardial infarction [65] reported that the FADS2 genotype can predict the beneficial effects of the omega-3.…”
Section: Introductionmentioning
confidence: 99%
“…Direct supplementation of foods rich in LA and ALA is the efficient way to obtain LA/ALA ratio in body. The commonly oils are rich in LA and poor in ALA, such as soybean and corn oils . Blasbalg et al found that LA intake increased 158% from 2.79% to 7.21% of energy, and ALA intake increased 85% from 0.39% to 0.72% in 1909 and 1999, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Preferably, surrogate AD biomarkers and disease mechanisms should be identified and shown to be altered after intervention with an appropriate omega-3 dose for the required time. There is a need for personalized AD intervention because of genetic dependence of omega-3 metabolism [3]. Non-invasive monitor of brain omega-3 contents using PET scans and other functional brain imaging modalities [6] are highly recommended approaches open for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of PUFAs are also controlled by the rate limiting enzyme, delta-6 desaturase. Desaturase haplotypes regulate omega fatty levels in different races [3]. Moreover, most Western diets are high in lipids and loaded with omega-6 PUFAs.…”
Section: Short Communicationmentioning
confidence: 99%